7(4-3*4)=-8(2*4-1)

Simple and best practice solution for 7(4-3*4)=-8(2*4-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(4-3*4)=-8(2*4-1) equation:


7(4-3*4)=-8(2*4-1)

We simplify the equation to the form, which is simple to understand
7(4-3*4)=-8(2*4-1)

Simplifying:
7*(4-12)=-8*(2*4-1)

Simplifying:
7*(4-12)=-8*(+8-1)

Simplifying terms in parentheses
7*(-8)=-8*(+8-1)

Simplifying terms in parentheses
7*(-8)=-8*(+7)

Reorder the terms in parentheses
+(-56)=-8*(+7)

Remove unnecessary parentheses
-56=-8+*(+7+)

Reorder the terms in parentheses
-56=+(-56)

Remove unnecessary parentheses
-56=-56

We move all terms containing to the left and all other terms to the right.
0=-56+56

We simplify left and right side of the equation.
0=0

0=0

This equation is an identity, so all real numbers are solutions.

See similar equations:

| X/7-8=-7 | | 25500+1200x=47900 | | 9+3(z-3)=-4z+1 | | 6-(2/9v)=-14 | | (8x+5)+(3x+8)=90 | | Z+20=4 | | 4c/3-7=5 | | -5n-2=-42 | | x^2-3x+8=x^2-5x+10+2x-2 | | -8(2f+3)=4(-8+54f) | | 4(5-2v)-6v=4(-7v-5)+6v | | 14/7 | | f(d)=-2d-3 | | 4x+4x-5=27 | | -12+4e+10-7e= | | 1-m=6-6 | | -2(4-11)= | | 7x+10=-5x-86 | | -12x-19=-57 | | 36.663=p+11.363 | | d=-2d-3 | | x^2-3x+8=x^2-5x+10+2x+2 | | 4y-70=12y-3 | | y+13=98 | | 4+x/6=5 | | 1-5r=11 | | -18+o=18 | | 6+6x=4x+0 | | 6-4d=16+9d | | x^2-310x+24025=0 | | -12k+14k= | | 4+4=5 |

Equations solver categories